The Ritz-Carlton: An organizational behavioural analysis - De Castro, Nicole (Animo Repository, 2023)
This paper shall demonstrate through the principles of organisational behaviour how the Ritz-Carlton was successful in establishing a leadership brand that empowers employees to become leaders in providing exceptional customer service. By providing empowering leadership, enacting customer-centric philosophies and values as well as maintaining a communication style that keeps the work force focused on the company goals, the Ritz has grown to become one of the finest brands in the world. As the leader in the hospitality industry, the Ritz-Carlton has become the gold standard because of their Gold Standards, which highlight the distinctive values that are the cornerstone of their organisation in the delivery of customer service.